2015
DOI: 10.17261/pressacademia.2015211617
|View full text |Cite
|
Sign up to set email alerts
|

Financial Differences and Similarities of Islamic Banks: A Study on Qismut Countries

Abstract: Six countries, namely Qatar, Indonesia, Saudi Arabia, Malaysia, UAE and Turkey (abbreviated as QISMUT) are considered to play an important role in the future international development of the Islamic finance. QISMUT countries have a majority Muslim population who prefers Islamic finance for their banking needs. QISMUT countries account for 38 million customers which is 67% of the global Islamic bank customer base. The focus of this study is to define similar (or different) international banks using the financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Bahrini (2017) also found that pure technical efficiency was less than scale efficiency in Islamic banks. Contrarily, Yildrim (2017) reported scale efficiency score to be lower than pure technical efficiency.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Bahrini (2017) also found that pure technical efficiency was less than scale efficiency in Islamic banks. Contrarily, Yildrim (2017) reported scale efficiency score to be lower than pure technical efficiency.…”
Section: Literature Reviewmentioning
confidence: 98%
“…This means that inefficiency resulted majorly from pure technical inefficiency. In another study, Yildrim (2017) found that Islamic banks in Qatar, Indonesia, Saudi Arabia, Malaysia, UAE and Turkey (QISMUT countries) failed in the area of managerial efficiency as they were also not able to produce on sufficient scale. Effendi (2016) reported high technical efficiency for Islamic rural banks in Indonesia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of the ROI ratio normality test showed a statistical value test of 0.274 with a significant probability of 0.125 and a value above 0.05 or value of α> 0.05. This means that the H0 is not rejected or the ROI variable is normally distribute [29].…”
Section: Independent Samples Testmentioning
confidence: 99%